A Model of Affirmative Intersectional Rehabilitation Counseling With Sexual Minorities: A Grounded Theory Study. (April 2016) - Dispenza, Franco; Viehl, Cory; Sewell, Miriam H.; Burke, Meredith A.; Gaudet, Megan M.
Sexual minority persons (i.e., lesbian, gay, bisexual, queer [LGBQ]) are at risk for developing chronic illness(es) and/or disabilities (CID); however, there is a dearth of information regarding the practices used by rehabilitation counselors working with this population. This modified grounded theory study aimed to understand the effective practices that rehabilitation counselors reported exhibiting when working with sexual minority persons living with CID. A total of 12 certified rehabilitation counselors were individually interviewed. Interviews were transcribed and recursively analyzed with a research team. Trustworthiness and credibility were ensured via in-depth member checking, researcher triangulation, and collection of rich descriptions from participants. A substantive model of rehabilitation counseling was constructed from the interviews, with Affirmative Intersectionality as the core category. Four supporting categories were also constructed, including professional attributes, alliance, intersectional sensitivity, and intersectional interventions . Details regarding the model are provided, as well as discussion on educational and supervision implications, study's limitations, and future research implications.